Ammonia-oxidizing archaea have more important role than ammonia-oxidizing bacteria in ammonia oxidation of strongly acidic soils - Zhang, Li-Mei; Hu, Hang-Wei; Shen, Ju-Pei; He, Ji-Zheng (The ISME Journal, 2012)
Increasing evidence demonstrated the involvement of ammonia-oxidizing archaea (AOA) in the global nitrogen cycle, but the relative contributions of AOA and ammonia-oxidizing bacteria (AOB) to ammonia oxidation are still in debate. Previous studies suggest that AOA would be more adapted to ammonia-limited oligotrophic conditions, which seems to be favored by protonation of ammonia, turning into ammonium in low-pH environments. Here, we investigated the autotrophic nitrification activity of AOA and AOB in five strongly acidic soils (pH<4.50) during microcosm incubation for 30 days. Significantly positive correlations between nitrate concentration and amoA gene abundance of AOA, but not of AOB, were observed during the active nitrification. 13 CO 2 -DNA-stable isotope probing results showed significant assimilation of 13 C-labeled carbon source into the amoA gene of AOA, but not of AOB, in one of the selected soil samples. High levels of thaumarchaeal amoA gene abundance were observed during the active nitrification, coupled with increasing intensity of two denaturing gradient gel electrophoresis bands for specific thaumarchaeal community. Addition of the nitrification inhibitor dicyandiamide (DCD) completely inhibited the nitrification activity and CO 2 fixation by AOA, accompanied by decreasing thaumarchaeal amoA gene abundance. Bacterial amoA gene abundance decreased in all microcosms irrespective of DCD addition, and mostly showed no correlation with nitrate concentrations. Phylogenetic analysis of thaumarchaeal amoA gene and 16S rRNA gene revealed active 13 CO 2 -labeled AOA belonged to groups 1.1a-associated and 1.1b. Taken together, these results provided strong evidence that AOA have a more important role than AOB in autotrophic ammonia oxidation in strongly acidic soils.